Pengaruh Jumlah Umkm dan Tingkat Partisipasi Angkatan Kerja Terhadap Pertumbuhan Ekonomi di Jawa Timur Tahun 2021-2023 - Ainur Rizqiyatul Jannah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study examines the influence of the number of Micro, Small, and Medium Enterprises (MSMEs) and the labor force participation rate on economic growth in East Java Province during the 2021-2023 period. This period represents economic recovery phase. Although economic growth has begun to show a positive trend, the exact factors driving this increase remain unknown. This study used panel data regression analysis with EViews 14 software. Document-based data collection methods were obtained from the Central Statistics Agency (BPS) of East Java Province, which covers 38 regencies/cities during 2021-2023. The results of this indicate that, partially, only the number of MSME significantly influences economic growth in East Java. Meanwhile, the labor force participation rate (TPAK) does not significantly influence economic growth in East Java. However, simultaneously, the number of MSME and TPAK significantly influence economic growth in East Java from 2021-2023. MSME play a crucial role in driving economic growth in East Java during the economic recovery period. Therefore, strengthening the MSME sector is an important strategy in supporting regional economic growth. This study examines the influence of the number of Micro, Small, and Medium Enterprises (MSMEs) and the labor force participation rate on economic growth in East Java Province during the 2021-2023 period. This period represents economic recovery phase. Although economic growth has begun to show a positive trend, the exact factors driving this increase remain unknown. This study used panel data regression analysis with EViews 14 software. Document-based data collection methods were obtained from the Central Statistics Agency (BPS) of East Java Province, which covers 38 regencies/cities during 2021-2023. The results of this study indicate that, partially, only the number of MSME significantly influences economic growth in East Java. Meanwhile, the labor force participation rate (TPAK) does not significantly influence economic growth in East Java. However, simultaneously, the number of MSME and TPAK significantly influence economic growth in East Java from 2021-2023. MSME play a crucial role in driving economic growth in East Java during the economic recovery period. Therefore, strengthening the MSME sector is an important strategy in supporting regional economic growth.
:: Finalisasi file repositori 22 Juli 2026_Kurnadi
Keywords: TPAK; economic growth; MSME; East Java